Revisiting intrathecal neurolysis for refractory cancer pain: A case series. (1st November 2020) - Woodford, Rachel; Curley, Daniel
Abstract : Purpose: Infiltration of phenol into the intrathecal space to perform a chemical rhizotomy is an uncommon but nevertheless potentially effective method of analgesia, particularly for opioid-refractory cancer pain. Due to the evolution of analgesics and other strategies directed at unresponsive pain, this procedure has largely fallen out of favour and no recent examination has been published in the literature. Method: In this case series we present four patients selected from a specialist palliative medicine service with refractory pain due to the presence of advanced malignancy involving the spine, who underwent this procedure. Through a comparison of reduction in opioid requirement, we aim to quantify the benefit of intrathecal neurolysis. Results: Pre- and post-procedural opioid requirements, expressed as oral morphine equivalent (OME) per standard calculations, were analysed retrospectively as a surrogate marker of procedural efficacy. An average 77% reduction in opioid requirement was noted following neurolysis, with a range of 65.6–86.7%. Conclusions: For appropriately selected patients, intrathecal neurolysis should remain a consideration for the palliative medicine physician for the management of intractable and refractory cancer-related pain.